Vertical velocities associated with gravity waves measured in the mesosphere and lower thermosphere with the EISCAT VHF radar - N. J. Mitchell; V. St. C. Howells (Annales Geophysicae, 1998)
The EISCAT VHF radar (69.4°N, 19.1°E) has been used to record vertical winds at mesopause heights on a total of 31 days between June 1990 and January 1993. The data reveal a motion field dominated by quasi-monochromatic gravity waves with representative apparent periods of ~30–40 min, amplitudes of up to ~2.5 m s –1 and large vertical wavelength. In some instances waves appear to be ducted. Vertical profiles of the vertical-velocity variance display a variety of forms, with little indication of systematic wave growth with height. Daily mean variance profiles evaluated for consecutive days of recording show that the general shape of the variance profiles persists over several days. The mean variance evaluated over a 10 km height range has values from 1.2 m 2 s –2 to 6.5 m 2 s –2 and suggests a semi-annual seasonal cycle with equinoctial minima and solsticial maxima. The mean vertical wavenumber spectrum evaluated at heights up to 86 km has a slope (spectral index) of –1.36 ± 0.2, consistent with observations at lower heights but disagreeing with the predictions of a number of saturation theories advanced to explain gravity-wave spectra. The spectral slopes evaluated for individual days have a range of values, and steeper slopes are observed in summer than in winter. The spectra also appear to be generally steeper on days with lower mean vertical-velocity variance. Key words. Meteorology and atmospheric dynamics (middle atmosphere dynamics; waves and tides)